THE EFFECT OF ATTITUDES, ORGANIZATIONAL COMMITMENTS, SEVERITY OF CHEATING LEVELS, PERSONAL COST OF REPORTING AND JOB COMMITMENT TO WHISTLEBLOWING INTENTIONS - Komarudin Mustopa; Asep Kurniawan; Trisandi Eka Putri (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This study aims to determine the effect of Attitudes, Organizational Commitments, Severity of Cheating Levels, Personal Cost of Reporting and Professional Commitment to whistleblowing intentions. Data collection techniques are questionnaires. The population in this study were all Village government apparatus in Subang Regency and the sample in this study were 200 respondents. Hypothesis testing uses multiple regression analysis. The results of this study indicate: (1) attitude influences the intention to conduct whistleblowing; (2) organizational commitment does not affect the intention to conduct whistleblowing; (3) Fraud severity level influences the intention to conduct whistleblowing; Personal Cost of Reporting has a negative effect on the intention to do a whistleblowing; (5) Job commitment influences the intention to conduct whistleblowing